Plataforma de Monitorização de Recursos num Sistema Message Oriented Middleware - Paulo Bordalo Marcos (2016)
The communication between devices has increased a lot in recent years, each time with more force. With the constant evolution of technologies and with the increase of capable devices, the volume of data that goes from machine to machine can reach significant levels. The mxfSPEEDRAIL developed by MOG Technologies, is an ingest video platform used by major broadcasters around the world. Architected as a distributed system, this product relies most of its functionality on communication between devices. Because of this, a good transmission of information is critical. Together with an ideology of progress, it is proposed a study of the best communication solutions that can meet the demands of its customers. There are technologies on the market, called Message Brokers, that promise to bring greater speed, fault tolerance and security in communication. An analysis of features and characteristics will be the first step towards an implementation choice. Working together with these technologies, it is essential to provide a resource management module, to administrators of mxfSPEEDRAIL, that will help the control system status.